Development of RNA binding proteins expression signature for prognosis prediction in gastric cancer patients - Zhou, Liqiang (Am J Transl Res, 2020)
It was reported that the expression of RNA binding proteins (RBPs) in malignant tumors is dysregulated and is closely related to tumorigenesis. However, some studies have confirmed the role of RBPs in gastric cancer (GC). We obtained data on gastric cancer in The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx), and identified RBPs that are dysregulated between gastric normal and cancer tissues. Then, we systematically investigated the expression characteristics and clinical prognostic potential of these RBPs through bioinformatics methods. We found 278 dysregulated RBPs in the GC, 91 of which were up-regulated and 181 were down-regulated. We detected 4 hub RBPs (HNRNPL, PABPN1, PCF, SNRPN) are related to overall survival (OS), and 3 hub RBPs (EEF1A2, MRPS5, PCF1) are related to disease-specific survival (DSS), and furthermore, we constructed prognostic signatures. Analysis of the OS and DSS signature showed that the GC patients with high-risk groups have worse OS and DSS than the low-risk groups. The receiver operator characteristic (ROC) curves of the 5-year survival rate of OS and DSS prognosis signature were drawn, and the areas under the two curves were 0.62 and 0.64, respectively. We constructed nomograms to predict OS and DSS, and evaluated by the calibration curve, which showed the GC prediction ability of these two models. Furthermore, the expression of the above six genes was verified by PCR, which is consistent with our results.